Clinical application of the COPD assessment test: longitudinal data from the COPD History Assessment in Spain (CHAIN) cohort - de Torres, Juan P; Marin, Jose M; Martinez-Gonzalez, Cristina; de Lucas-Ramos, Pilar; Mir-Viladrich, Isabel; Cosio, Borja; Peces-Barba, German; Calle-Rubio, Miryam; Solanes-García, Ingrid; Agüero Balbin, Ramón; de Diego-Damia, Alfredo; Feu-Collado, Nuria; et al. (Chest, 2014)
The COPD Assessment Test (CAT) has been proposed for assessing health status in COPD, but little is known about its longitudinal changes. The objective of this study was to evaluate 1-year CAT variability in patients with stable COPD and to relate its variations to changes in other disease markers. We evaluated the following variables in smokers with and without COPD at baseline and after 1 year: CAT score, age, sex, smoking status, pack-year history, BMI, modified Medical Research Council (mMRC) scale, 6-min walk distance (6MWD), lung function, BODE (BMI, obstruction, dyspnea, exercise capacity) index, hospital admissions, Hospital and Depression Scale, and the Charlson comorbidity index. In patients with COPD, we explored the association of CAT scores and 1-year changes in the studied parameters. A total of 824 smokers with COPD and 126 without COPD were evaluated at baseline and 441 smokers with COPD and 66 without COPD 1 year later. At 1 year, CAT scores for patients with COPD were similar (± 4 points) in 56%, higher in 27%, and lower in 17%. Of note, mMRC scale scores were similar (± 1 point) in 46% of patients, worse in 36%, and better in 18% at 1 year. One-year CAT changes were best predicted by changes in mMRC scale scores (β-coefficient, 0.47; P < .001). Similar results were found for CAT and mMRC scale score in smokers without COPD. One-year longitudinal data show variability in CAT scores among patients with stable COPD similar to mMRC scale score, which is the best predictor of 1-year CAT changes. Further longitudinal studies should confirm long-term CAT variability and its clinical applicability. ClinicalTrials.gov; No.: NCT01122758; URL: www.clinicaltrials.gov.